جدلية العقل العلمي في فلسفة العلوم المعاصرة -نموذج غاستون باشلار- - عبد العزيز بوالشعير (مجلة الآداب و العلوم الإجتماعية, 2015)
This paper aims to shed light on the dialectic of scientific reason in the philosophy of contemporary science through Gaston Bachelard’s model. This model shows the impact of scientific knowledge in the structure of thought which reveals the new epistemological values that make the reason, putting its philosophical position into question whenever the scientific thought results new theories and attitudes that oblige it to reconsider its structure and content in order to be kept up to scientific revolutions. All this require from the reason to be revolutionary, renewed and developed. This means that reason and reality are no longer the same as they were in the classical philosophy and science.